Development and Impact of an Institutional Enhanced Recovery Program on Opioid Use, Length of Stay, and Hospital Costs Within an Academic Medical Center: A Cohort Analysis of 7774 Patients. (February 2021) - Thiele, Robert H.; Sarosiek, Bethany M.; Modesitt, Susan C.; McMurry, Timothy L.; Tiouririne, Mohamed; Martin, Linda W.; Blank, Randal S.; Shilling, Ashley; Browne, James A.; Bogdonoff, David L.; Bauer, Todd W.; Hedrick, Traci L.
Abstract : BACKGROUND: Enhanced Recovery (ER) is a change management framework in which a multidisciplinary team of stakeholders utilizes evidence-based medicine to protocolize all aspects of a surgical care to allow more rapid return of function. While service-specific reports of ER adoption are common, institutional-wide adoption is complex, and reports of institution-wide ER adoption are lacking in the United States. We hypothesized that ER principles were generalizable across an institution and could be implemented across a multitude of surgical disciplines with improvements in length of stay, opioid consumption, and cost of care. METHODS: Following the establishment of a formal institutional ER program, ER was adopted in 9 distinct surgical subspecialties over 5 years at an academic medical center. We compared length of stay, opioid consumption, and total cost of care in all surgical subspecialties as a function of time using a segmented regression/interrupted time series statistical model. RESULTS: There were 7774 patients among 9 distinct surgical populations including 2155 patients in the pre-ER cohort and 5619 patients in the post-ER cohort. The introduction of an ER protocol was associated with several significant changes: a reduction in length of stay in 5 of 9 specialties; reduction in opioid consumption in 8 specialties; no change or reduction in maximum patient-reported pain scores; and reduction or no change in hospital costs in all specialties. The ER program was associated with an aggregate increase in profit over the study period. CONCLUSIONS: Institution-wide efforts to adopt ER can generate significant improvements in patient care, opioid consumption, hospital capacity, and profitability within a large academic medical center.